A Study of Hadith on Islamic Law Regarding Kafa’ah and Khitbah (Engagement) - Ihda Ihromi; Muhammad Irgan Aunul Fiqri (Ad-dawl : Jurnal Islamic Studies, 2026)
This study aims to examine the ahkam hadiths related to the concepts of kafa’ah and khitbah in Islamic marriage, as well as to understand their legal implications in building a harmonious family. The method used is qualitative research with a library research approach, sourced from hadith books, classical and contemporary fiqh books, and relevant scientific literature. The approaches used include takhrij and syarah hadith analysis to assess the quality and meaning of the hadiths, as well as a normative approach to explore their legal implications. The results of the study indicate that kafa’ah is the compatibility between prospective husband and wife, which includes aspects of religion, lineage, wealth, occupation, and physical condition, functioning as a supporting factor in creating a sakinah, mawaddah, and warahmah family, although it is not a requirement for the validity of marriage. Meanwhile, khitbah is a proposal process recommended in Islam as a means of getting to know each other before marriage, with certain provisions and ethics that must be observed. Therefore, a proper understanding of the concepts of kafa’ah and khitbah can serve as a foundation for building a harmonious and sustainable household.